Intervensi Untuk Mengatasi Dampak Pada Anak Yang Mengalami Kekerasan Dalam Rumah Tangga (KDRT) - Dwintya Saffira Tulangow; Adila Anbar Syafitri; Aisyah Latifa Amalia; Arliana Ardani; Chintya Marethania Putri; Dewi Ayu Tri Cahyani; Dinda Zulyarnis; Dunna Izafira; Eza Wahyuriyani; Fathya Khadijah Laleno; Felis May Safitri; Fitri Amalia; Fitria Alda Safira; Intannia Ani Sagita; Joelita Tri Hardani; Renta Sianturi (AKPER Pasar Rebo, 2022)
In children, the incidence of acts of violence (KDRT) is the main thing to worry about and is getting more serious from time to time. Violence that occurs in children (KDRT), which is so increasing, can inhibit the growth and development of children both cognitively, psychomotor, emotional, socially and morally. The purpose of this literature is to analyze theoretically what therapies can be used to help overcome the impact of domestic violence on children. The method in writing this article is a simple Literature Review. By analyzing 10 articles related to effective therapy to reduce the impact on children of domestic violence. The result is that all the therapies that have been analyzed are quite effective in overcoming the impact on children who experience domestic violence (KDRT). The average results in the group of children who experienced domestic violence (KDRT) who were given the intervention were quite significant. The conclusion from the literature review is that all the therapies that have been analyzed have an effect on overcoming the impact on children who experience violence. This literature review recommendation can be used as an additional intervention or alternative therapy that can be used in children with domestic violence problems. Keywords : Child, Conseling, Domestic Violence, Intervention, and , Therapy